2011
DOI: 10.1007/s00127-011-0412-6
|View full text |Cite
|
Sign up to set email alerts
|

The Portuguese version of the Personal and Social Performance Scale (PSP): reliability, validity, and relationship with cognitive measures in hospitalized and community schizophrenia patients

Abstract: The present study supports the reliability and validity of the Portuguese language version of the PSP and further supports the original measure. The co-administration of brief cognitive assessments with measures of functioning may lead to more focused interventions, possibly improving outcomes in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
0
38
0
1
Order By: Relevance
“…Other studies have agreed with the results from this study that positive symptoms do not have an impact on social functioning as strong as negative symptoms (Rabinowitz, Berardo, Bugarski, & Marder, ). The negative correlation between the PSP‐CHN global score and the PANSS cognitive factor lends credence to the idea that social functioning is important to cognition in SZ (Brissos et al, ).…”
Section: Discussionmentioning
confidence: 54%
“…Other studies have agreed with the results from this study that positive symptoms do not have an impact on social functioning as strong as negative symptoms (Rabinowitz, Berardo, Bugarski, & Marder, ). The negative correlation between the PSP‐CHN global score and the PANSS cognitive factor lends credence to the idea that social functioning is important to cognition in SZ (Brissos et al, ).…”
Section: Discussionmentioning
confidence: 54%
“…In addition, the rater can assess one global score as well as subscores of the four domains: socially useful activities, personal and social relationships, self-care, and disturbing and aggressive behaviors, to be a more specific rating scale for functioning in comparison to the GAF scale and SOFAS. The reliability and validity of the PSP scale have been investigated in several studies, which have confirmed its high test-retest reliability, good inter-rater reliability validity (Morosini et al, 2000;Srisurapanont et al, 2008;Brissos et al, 2012), and high correlations with the GAF scale, SOFAS, MiniInternational Classification of Functioning-Rating for Mental Disorders (Mini-ICF-P), and Positive and Negative Syndrome Scale (PANSS) (Nasrallah et al, 2008;Apiquian et al, 2009;Patrick et al, 2009;Garcia-Portilla et al, 2011;Nafees et al, 2012;Wu et al, 2013). The PSP scale offers an efficient method of monitoring both psychosocial functioning in the acute phase and continuing treatment of schizophrenia (Kawata and Revicki, 2008;Nasrallah et al, 2008;Patrick et al, 2009), and has been translated into different languages, including German , Spanish (Apiquian et al, 2009), Portuguese (Brissos et al, 2012), Thai (Srisurapanont et al, 2008), Chinese (Tianmei et al, 2011), and Taiwanese Mandarin (Hsieh et al, 2011;Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…This is a global scale to measure psychological, social and occupational functioning on a hypothetical continuum ranging from 0 (maximal dysfunction from mental illness) to 100 (high functioning and health) (Jones et al, 1995), with evidence for concurrent validity to assess functioning in patients suffering from schizophrenia (Startup et al, 2002). Portuguese translations of psychometric instruments, with extensive prior use in patients suffering from SMI (Gago, 1996; Fernandes et al, 2009; Brissos et al, 2012; Talina et al, 2013; Cardoso et al, 2016), were used.…”
Section: Methodsmentioning
confidence: 99%